Sustainable Energy Crop Production in Poland: Perspectives; Perspektywa zroẃnowazȯnej produkcji rosĺin energetycznych w Polsce - Agata Pszczoĺkowska; Zdzisława Romanowska-Duda; Wiktor Pszczoĺkowski; Mieczysław Grzesik; Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
In the context of achieving the targets of the energy economy, Poland's demand for bioenergy is stimulated by several factors, including the biomass potential of agricultural cultivation. The objective of this article is to indicate perspectives for the sustainable production of energy crops in Poland through the production of total biomass as the main renewable source of energy utilized in the countries of Europe and supported by Directive 2009/28/EC of the European Parliament and of the Council of April 23, 2009 on the Promotion of the Use of Energy from Renewable Sources, currently in force. The most important reasons for promoting the production of plant biomass for energy purposes is the desire to work against climate change and reduce the emission of greenhouse gasses. This article indicates the significant role of Life Cycle Assessment (LCA) in biofuels and their production. Note is also taken of agro- climatic and soil conditions for the production of biomass in Poland as well as the economic aspects using the Agricultural Production Space Valuation Ratio (APSVR). – – Zapotrzebowanie w Polsce na bioenergie w konteksćie realizacji celoẃ gospodarki energetycznej jest stymulowane przez szereg czynnikoẃ, w tym potencjał biomasy pochodzacy z upraw rolniczych. Celem artykułu jest wskazanie na perspektywe zroẃnowazȯnej produkcji rosĺin energetycznych w Polsce poprzez produkcje całkowitej biomasy jako głoẃnego odnawialnego zŕod́ła energii wykorzystywanego w krajach Europy, a wspieranego przez obecnie obowiazujaca Dyrektywe Parlamentu Europejskiego i Rady 2009/28/WE z dnia 23 kwietnia 2009 r. w sprawie promowania stosowania energii ze zŕod́eł odnawialnych (OZÉ). Najistotniejszymi powodami promowania produkcji biomasy rosĺinnej na cele energetyczne jest checṕrzeciwdziałania zmianom klimatycznym i redukcja emisji gazoẃ cieplarnianych. W artykule wskazano na znaczna role analizy LCA (Life Cycle Assessment) dla biopaliw i ich produkcji. Zwroćono uwage na warunki agroklimatyczne i glebowe uwarunkowania produkcji biomasy w Polsce oraz ekonomiczny aspekt jakim jest wskazńik waloryzacji rolniczej przestrzeni produkcyjnej (WWRPP).
Keywords: 330